Male breast cancer: a clinicopathological study of an Egyptian population (Alexandria experience) - Soliman, Maher; Hetnał, Marcin (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : The purpose of this retrospective study is to evaluate the clinicopathological features and treatment results of male breast cancer presented to our tertiary referral center. Material and methods : Between January 1998 and December 2005, a total of 39 men with breast cancer treated at Alexandria Main University Hospital and their medical records were reviewed. Results : The median age of patients was 59 years. Only 3 (7.7%) patients had positive family history. All patients presented by breast swellings that were associated with axillary mass in about one third of them. Around 80% had hormone receptor positive (estrogen and/or progesterone receptors). Two third of patients had advanced T-stage (T3 and T4). Left sided breast cancer occurred in 51.3%. Infiltrating ductal carcinoma was the most common type of histology encountered and grade 2 was the predominant grade of tumor. Modified radical mastectomy was the most common (87.2%) type of surgery done followed by chemotherapy for 32 patients and loco-regional radiotherapy for 20 patients. Tamoxifen was administered in 31 patients. Distant relapse occurred in 7 patients (17.9%) and local recurrence occurred in 2 patients (5.1%). The 5-year disease-free survival (DFS) was 82% and the 5-year overall survival (OS) rate was 84%. Only negative axillary lymph node and positive hormone receptor status were significantly associated with favorable DFS and OS. T-stage, grade of tumor and type of chemotherapy given had no statistically significant impact on either DFS or OS. Conclusions : Male breast cancer is still under-investigated and further researches are warranted.